Caution in Using the Activated Partial Thromboplastin Time to Monitor Argatroban in COVID-19 and Vaccine-Induced Immune Thrombocytopenia and Thrombosis (VITT). (December 2021) - Guy, Susan; Kitchen, Steve; Makris, Michael; M. Maclean, Rhona; Saccullo, Giorgia; Vanveen, Joost J
Introduction: Argatroban is licensed for patients with heparin-induced thrombocytopenia and is conventionally monitored by activated partial thromboplastin time (APTT) ratio. The target range is 1.5 to 3.0 times the patients' baseline APTT and not exceeding 100 s, however this baseline is not always known. APTT is known to plateau at higher levels of argatroban, and is influenced by coagulopathies, lupus anticoagulant and raised FVIII levels. It has been used as a treatment for COVID-19 and Vaccine-induced Immune Thrombocytopenia and Thrombosis (VITT). Some recent publications have favored the use of anti-IIa methods to determine the plasma drug concentration of argatroban. Methods: Plasma of 60 samples from 3 COVID-19 patients and 54 samples from 5 VITT patients were tested by APTT ratio and anti-IIa method (dilute thrombin time dTT). Actin FS APTT ratios were derived from the baseline APTT of the patient and the mean normal APTT. Results: Mean APTT ratio derived from baseline was 1.71 (COVID-19), 1.33 (VITT) compared to APTT ratio by mean normal 1.65 (COVID-19), 1.48 (VITT). dTT mean concentration was 0.64 µg/ml (COVID-19) 0.53 µg/ml (VITT) with poor correlations to COVID-19 baseline APTT ratio r 2 = 0.1526 p <0.0001, mean normal r 2 = 0.2188 p < 0.0001; VITT baseline APTT ratio r 2 = 0.04 p < 0.001, VITT mean normal r 2 = 0.0064 p < 0.001. Conclusions: We believe that dTT is a superior method to monitor the concentration of argatroban, we have demonstrated significant differences between APTT ratios and dTT levels, which could have clinical impact. This is especially so in COVID-19 and VITT.